Violent extremism: a comparison of approaches to assessing and managing risk - Logan, Caroline (Legal and criminological psychology, 2019)
Purpose. The task of assessing and managing risk of violence has evolved considerably in the last 25 years, and the field of violent extremism has the potential to stand on the shoulders of the giants of this time. Therefore, the objective of this study was to identify good practice in the risk field and to apply that to the specific area of risk in relation to violent extremism – in order that developments here accord to highest standards of practice achieved so far elsewhere. Method and Results. We begin by addressing the essential requirement to define the task of assessing and managing the risk of violent extremism – What is its purpose and parameters, who are its practitioners, in what contexts is this activity delivered, and how might any such context both facilitate and hinder the objectives of the task? Next, we map the terrain – What guidance is already available to assist practitioners in their work of understanding and managing the risk of violent extremism, and by what standards may we judge the quality of this and future guidance in the contexts in which is it applied? Finally, we explore options for the development of the field in terms of the empirical basis upon which the risks presented by individuals and the organizations to which they may affiliate are assessed, understood, and managed. Conclusions. Recommendations are proposed in relation to each of these three areas of concern with a view to supporting the rapid and credible advancement of this growing and vital area of endeavour.